Comparative Analysis of Ideologies behind the Depiction of Still Life in European Painting and Islamic Decoration: 16th - 18th Century (Al-Qamar, 2022)
Still life representation from sixteenth to the eighteenth centuries, either in paintings or as decorative motifs, has diverse ideological approaches. This genre appears in two different geographical regions both within these centuries contemporary to each other: Europe and South Asia. The research focuses on the novel idea of creating an analogy between the connotations beheld by both European and Mughal still life objects in visual portrayal. Still life painting emerged with a religious and moral approach in sixteenth century Europe as a result of Protestant Reformation. While in South Asia during the Mughal rule, it originated as a foreign decorative element from Persia, where it had symbolic associations for the terrestrial and celestial life. The noble ideology of both the European and Islamic still life gradually shifted towards a materialistic approach, under the influence of respective patronage during the seventeenth and eighteenth centuries. The lack of scholarship on the subject matter inspired this study, which will contribute to elaborate how this genre has evolved to embody diverse concepts. The analytical study on the representation of still life in both European painting and Islamic decoration under the Mughals, based on the formal qualities and corresponding ideologies will be a valuable perspective for existing art historical scholarship. Not only will the research be beneficial in studying the genre but will also create a holistic view of the changing thought perspective globally during the sixteenth to eighteenth centuries.
Keywords: Still life motifs; Still life painting; European painting; Mughal decoration; Vanitas paintings.